Analisis Budaya Organisasi Terhadap Kinerja Karyawan Koperasi Di Banteng Muda Indonesia Mandiri - efrin Tarigan; Muhammad Agung Anggoro (CERED Indonesia Institute, 2022)
In this era the number of cooperatives that exist in the community, enables cooperatives to compete and survive in the midst of the many types of businesses that stand and are similar to cooperatives. Therefore, the cooperative's superiors and employees must be able to form an organization in which there is a team that is able to work together without feeling each other down. Therefore, the efforts made in improving and creating a comfortable work environment for employees is to provide comfort to employees without any pressure on employees who are comfortable with a work environment and a strong organizational culture within the company. In addition, employees must also be able to become a good organization for the community so that every customer gets good service from the organization. In addition, cooperatives also work as savings and loans provided for the community, this can help people to carry out savings and loan transactions who want to start a business or who already have their own business.